ANALYSIS OF THE IMPLEMENTATION OF REMISSION FOR INMATES IN THE LEGAL JURISDICTION OF THE MINISTRY OF LAW AND HUMAN RIGHTS IN THE SPECIAL REGION OF YOGYAKARTA - Murdoko (Media Inovasi Pendidikan dan Publikasi, 2024)
The analysis of the implementation of remission for inmates in the legal jurisdiction of the Ministry of Law and Human Rights in the Special Region of Yogyakarta explores the execution of remission for Correctional Inmates (WBP) in this region. The focus is on the reduction of sentences as a form of appreciation for inmates who demonstrate good performance, dedication, and discipline in rehabilitation programs, in accordance with applicable legal provisions. Remission is a crucial component of the correctional system as it provides inmates with the opportunity to reduce their sentences based on positive participation and behavior in rehabilitation. However, the implementation of remission raises concerns about justice, legal compliance, and its impact on inmates and society. This study aims to evaluate the implementation of remission in the region in a fair, transparent manner, and in accordance with legal provisions. With a rich cultural heritage, this area needs to ensure that the implementation of remission supports the rehabilitation of inmates to reintegrate into society productively and responsibly. This research employs a normative juridical approach to analyze how remission is regulated by law and how it adheres to prevailing legal principles. The emphasis on legal aspects allows the study to explore and evaluate the effectiveness, compliance, and practical impact of the implementation of remission for inmates in the jurisdiction of the Ministry of Law and Human Rights in the Special Region of Yogyakarta